Rapid Determination of the Furaltadone Metabolite in Aquatic Products Based on Fe3O4@AuNPs/MWCNTs-COOH Immunosensor - LI Ting, HE Huange, LU Hang, LI Shuguo (Shipin Kexue)
A nano-immunosensor for the rapid determination of 3-amino-5-methylmorpholino-2-oxazolidinone (AMOZ) in aquatic products was prepared by immobilizing anti-AMOZ antibodies onto a glass carbon electrode modified with a hybrid nanocomposite (Fe3O4@AuNPs/MWCNTs-COOH) consisting of magnetic ferric oxide (Fe3O4), gold nanoparticles (AuNPs), and carboxylated multi-walled carbon nanotubes (MWCNTs-COOH). The microstructure of the prepared nanoparticles of Fe3O4 and Fe3O4@AuNPs was analyzed using ultraviolet-visible (UV-vis) spectroscopy and infrared (IR) spectroscopy, and their microscopic morphology was characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The electrochemical performance of the prepared immunosensor was studied by cyclic voltammetry, electrochemical impedance spectroscopy, and the experimental conditions were optimized by differential pulse voltammetry using [Fe(CN)6]3-/4- as the probe. The optimized conditions were as follows: V(Fe3O4@AuNPs) to V(MWCNTs-COOH) ratio 1:2, electrolyte solution pH 7.0, antibody concentration 80 μg/mL, incubation temperature 37 ℃, and incubation time 30 minutes. Under these conditions, the current response of the immunosensor showed a good linear relationship with lg C[AMOZ] in the range from 1.0 × 10-10 to 8.0 × 10-7 mol/L, with a detection limit of 2.4 × 10-11 mol/L. The recovery rates of spiked crucian carp samples were between 92.78% and 102.61%, which was basically consistent with the results of high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Furthermore, the immunosensor method has the advantages of simple pre-treatment and fast detection speed, and can be used for the rapid detection of AMOZ in actual aquatic products.